2017
DOI: 10.1007/s12035-017-0715-z
|View full text |Cite|
|
Sign up to set email alerts
|

Short-Term Exposure to Enriched Environment in Adult Rats Restores MK-801-Induced Cognitive Deficits and GABAergic Interneuron Immunoreactivity Loss

Abstract: Perinatal injections of N-methyl-D-aspartate (NMDA) receptor antagonist in rodents emulate some cognitive impairments and neurochemical alterations, such as decreased GABAergic (gamma aminobutyric acid) interneuron immunoreactivity, also found in schizophrenia. These features are pervasive, and developing neuroprotective or neurorestorative strategies is of special interest. In this work, we aimed to investigate if a short exposure to enriched environment (EE) in early adulthood (P55-P73) was an effective stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 85 publications
(91 reference statements)
3
12
0
3
Order By: Relevance
“…In summary, present study further substantiated the nding that MK801 administration to neonatal mice could induce a negative model of schizophrenia 43,44,45 . Speci cally 22,23,31 , a consecutive 5-day administration protocol of MK801 in neonatal mice (P7) induced negative symptoms of schizophrenia including hypoactivity and less sociability.…”
Section: Discussionsupporting
confidence: 80%
“…In summary, present study further substantiated the nding that MK801 administration to neonatal mice could induce a negative model of schizophrenia 43,44,45 . Speci cally 22,23,31 , a consecutive 5-day administration protocol of MK801 in neonatal mice (P7) induced negative symptoms of schizophrenia including hypoactivity and less sociability.…”
Section: Discussionsupporting
confidence: 80%
“…Like others, our study confirms that MIA offspring are primarily impaired in behavior requiring attentional decision as with PPI and NOR. Canetta et al (2016) and Wallace et al (2014) demonstrated MIA offspring being deficient in attentional set shifting and reversal learning (Wallace et al, 2014) but no signs of deficits in working memory were evident (Canetta et al, 2016;Nakamura et al, 2021), the latter being in accordance with the lack of deficits we found with MWM test. Canetta et al (2016) further demonstrated an impaired GABAergic transmission in the mPFC of adult MIA offspring which was selective for PV-expressing interneurons.…”
Section: Summary Of Findings-differences Between Mia Offspring and Controlssupporting
confidence: 87%
“…This impression is supported by the findings of Kentner et al (2016) and Zhao et al (2020), demonstrating that housing MIA offspring in an enriched environment (EE) reverses the cognitive deficits in spatial discrimination and the down-regulation of genes critical to synaptic transmission and plasticity. Similarly, rodent studies using NMDA receptor antagonist dizolcilpine (MK-801) injection to induce a schizophrenia-like state demonstrated beneficial effects of EE, reversing the MK-801 induced deficits in NOR and PPI (Murueta-Goyena et al, 2018;Huang et al, 2021), accompanied by recovery of PV immunoreactivity. Interestingly, the same effect could be achieved by selective chemogenetic activation of PV-expressing interneurons within frontal association cortex (Huang et al, 2021).…”
Section: Summary Of Findings-effects Of Itbs At Adolescence or Adulthoodmentioning
confidence: 99%
“…This enduring effect in adult rats after peri-adolescent NMDA receptor disruption was reversed by increasing local GABAergic transmission in the PFC with a single local infusion of the GABAA positive allosteric modulator Indiplon. Evidence suggests that earlier disruption of NMDA signalling (via ketamine or MK-801 during the second-third postnatal week) has similar long-term effects in adulthood, reducing expression of PV, disrupting synaptic properties in interneurons, and causing disinhibition of pyramidal cells [72,73]. Taken together, these findings demonstrate (1) that GABAergic control of prefrontal excitability increases across development before reaching mature functional capacity in late adolescence, and (2) that sustained NMDA receptor transmission is critical for moderating the normal functional development of GABAergic inhibitory networks in the mPFC.…”
Section: Development Of Inhibitory Networkmentioning
confidence: 99%